Direct LAMP for on-site rapid detection of Vibrio parahaemolyticus in shrimp (Litopenaeus vannamei) aquaculture water - Xiaodan Pu; Feng Lu; Qianqian Yang; Zhenyu Han; Xueting Zhu; Jianlei Chen; Dahai Zhang; Xuzhi Zhang (PLoS ONE, 2026)
Effective on-site surveillance of pathogens in aquaculture environments via loop-mediated isothermal amplification (LAMP) remains challenging due to the impractical and time-intensive DNA extraction required in field settings. In this study, a DNA extraction-free approach, i.e., direct LAMP (dLAMP), was evaluated, additionally concerning key physicochemical inhibitors derived from real, complex aquaculture water matrices. Eight representative water samples were collected from Litopenaeus vannamei aquaculture systems, encompassing broad ranges of salinity (7.61‰–32.88‰), pH (6.98–8.41), chemical oxygen demand (COD: 6.00–12.25 mg/L), soluble reactive phosphate (SRP: 0.13–1.24 mg/L), dissolved inorganic nitrogen (DIN: 0.67–3.09 mg/L), and total suspended solids (TSS: 133–737 mg/L). Boiled aquaculture water samples served directly as DNA templates for the LAMP detection of Vibrio parahaemolyticus with tlh gene. While pH, COD, SRP, DIN, and TSS had negligible effects on amplification efficiency, elevated salinity was found to significantly reduce assay sensitivity. Adjusting the salinity using deionized water to ≤ 10.00‰ effectively mitigates its inhibitory effect. Under optimized conditions, 10 µL of boiled aquaculture water was sufficient for reliable detection without compromising sensitivity or specificity. The detection limit was determined to be 10 2 CFU/mL (with a detection probability of 67%). Using DNA dye GeneFinder™ to show amplicon visually, the entire workflow, including sampling, salinity adjustment (if needed), boiling, chilling, and isothermal incubation, required no more than 1 h. This dLAMP method requires no specialized equipment beyond a portable heater, demonstrating a strong potential for point-of-care applications, and enabling practical field surveillance of pathogens in aquaculture water.